1992
DOI: 10.3168/jds.s0022-0302(92)78085-0
|View full text |Cite
|
Sign up to set email alerts
|

Nonprotein Nitrogen and Protein Distribution in the Milk of Cows

Abstract: The NPN content of milk represents only 5 to 6% of the total N in milk. However, the significance of this milk N fraction to energy and N metabolism in the dairy cow has not been well characterized. The single largest contributor to the NPN fraction of milk NPN is urea. Urea equilibrates in body water, and blood urea is the primary source of milk urea. The urea in milk can be derived from at least two sources: the end product of digestion and amino acid catabolism. Blood urea N was positively associated with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
1
12

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(120 citation statements)
references
References 68 publications
8
99
1
12
Order By: Relevance
“…Some authors found that high environment temperatures reduced the total protein content and decreased the consistency of milk clots of four different breeds, which was lower in summer and higher in winter (DePeters and Cant, 1992;DePeters and Ferguson, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Some authors found that high environment temperatures reduced the total protein content and decreased the consistency of milk clots of four different breeds, which was lower in summer and higher in winter (DePeters and Cant, 1992;DePeters and Ferguson, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Milk urea nitrogen is primarily derived from BUN because urea equilibrates with water in the body. This equilibrium explains the high correlation between MUN and BUN concentrations (Depeters and Ferguson, 1992). Blood urea nitrogen derives from at least 2 sources: the liver detoxification of ammonia diffused from the rumen and the catabolism of AA in the liver (Depeters and Ferguson, 1992).…”
Section: Introductionmentioning
confidence: 91%
“…This equilibrium explains the high correlation between MUN and BUN concentrations (Depeters and Ferguson, 1992). Blood urea nitrogen derives from at least 2 sources: the liver detoxification of ammonia diffused from the rumen and the catabolism of AA in the liver (Depeters and Ferguson, 1992). Thereby, MU concentration could reflect protein metabolism in the cow and could be related to the diet.…”
Section: Introductionmentioning
confidence: 91%
“…In this study, the numeric increase in BUN which cows fed with alfalfa hay was expected because alfalfa hay has more rumen degradable protein (RDP) than corn silage (NRC, 2001) but the BUN might be compensated by similar starch and fermentable energy content of diets. DePeters and Ferguson (1992) reported that concentrations of ruminal NH 3 and BUN are highly correlated. In this study, the concentrations of ruminal NH 3 was not affected by the dietary treatments and ranged from 17.4 to 20.7 mg/dl (Gencoglu and Turkmen, 2006).…”
Section: Resultsmentioning
confidence: 99%